Coupling Mechanism of Rotating Casing Effect and Impeller Structure of Roto-Jet Pump - Qi Huang; Zailun Liu; Xiaobing Wang; Qifei Li; Hui Quan (Shock and Vibration)
An increase in internal pressure of a Roto-Jet pump is due to combined action of its impeller and rotating casing. Internal pressure of the pump chamber was determined according to outlet pressure of the impeller, and the influence of the rotary casing effect was ignored. To study the combined action mechanism of the rotating casing effect and impeller structure on the Roto-Jet pump, we used the open test bed of the Roto-Jet pump and four model pumps with impellers of different structures as research objects. We also conducted a comprehensive experimental study on the coupling mechanism between the rotating casing effect and impeller structure. Numerical calculation was performed to avoid the assumption of isotropic eddy viscosity, Reynolds stress linear pressure-strain model is selected, and the numerical calculation results are compared with the experimental results to verify its credibility. The results show that the rotating casing effect has multiple functions to reduce the friction loss of the disc, improve the pressure distribution inside the rotating casing, and increase the pump head. All scheme, pressure, and velocity fluctuations occur in the upstream and wake regions of the collecting pipe and the energy loss is concentrated in the upstream region. The difference in velocity distribution inside the collecting pipe is small and negligible. As long as the impeller and rotating casing continue to rotate synchronously, the liquid shear velocity at the same coordinate position of each scheme remains unchanged, and the liquid rotation angular velocity in the rotating casing is approximately 75% of the rotating casing which conforms to the rigid motion law. In the same scheme, the coefficient of uneven velocity inside the rotating casing gradually increases along the radial direction. The closer to the axis, the faster is the decrease of the peak tangential velocity and the velocity tends to be uniform. The size, shape, and position of the vortex core inside the rotating casing change constantly with various schemes. The distribution of vortex cores varies under each scheme. The front cover and rotating casing have a serious effect on the vortex core. The extremely poor analysis of the test results shows that the performance of the Roto-Jet pump is better when the closed impeller is rotated in synchronisation with the rotating casing. The advantages and disadvantages of each blade type can be determined according to the situation. The research results can exhibit the influence mechanism of the Roto-Jet pump shell effect. Selection of an impeller structure provides a reference.